1989
DOI: 10.1111/j.1469-8137.1989.tb04219.x
|View full text |Cite
|
Sign up to set email alerts
|

Chitin‐decomposing actinomycetes associated with a vesicular–arbuscular mycorrhizal fungus from a calcareous soil

Abstract: SUMMARY.Spores of Glomus macrocarpum Tul. & Tul. were sieved from a calcareous, silty clay loam soil, washed in sterile water, and plated on chitin agar for the isolation of actinomycetes. Of the 190 spores examined, 100 were colonized by one or more chitin-decomposing microorganisms: 82"/,, were colonized by actinomycetes, 17% by bacteria, and 1 "o hy fungi. Fifty-otie actitiomycete isolates were classified on the basis of morphological, cultural and biochemical criteria. Tentative identifications to genera a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…Bars (in micrometers): A and B, 50; C, 100; D, E, F, and G, 10; H and I, 1. (2) found that out of 190 spores examined, 100 were colonized by one or more chitin-decomposing microorganisms; 82% were colonized by actinomycetes, 17% by bacteria, and 1% by fungi. Carpenter-Boggs et al (7) demonstrated a positive correlation between higher germination rate and the amount of production of geosmin, CO 2 , and 2-methylisoborneol by the actinomycetes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bars (in micrometers): A and B, 50; C, 100; D, E, F, and G, 10; H and I, 1. (2) found that out of 190 spores examined, 100 were colonized by one or more chitin-decomposing microorganisms; 82% were colonized by actinomycetes, 17% by bacteria, and 1% by fungi. Carpenter-Boggs et al (7) demonstrated a positive correlation between higher germination rate and the amount of production of geosmin, CO 2 , and 2-methylisoborneol by the actinomycetes.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, some bacterial populations, called mycorrhiza helper bacteria, have beneficial effects on AMF growth not only by improving mycorrhizal root colonization and stimulating extraradical hyphal growth but also by facilitating AMF spore germination (11,12). The latter effect has been shown for Actinomycetes (2,7,22), Pseudomonas and Corynebacterium (21), and Bacillus (38) spp.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Since the 1970s, certain microorganisms, particularly bacteria, have been observed to live in close association with AMF. These bacteria are living on the surface of (or among) fungal spores and hyphae (Ames et al 1989;Andrade et al 1998), in the spore wall (Macdonald and Chandler 1981;Walley and Germida 1996), and even inside the fungal cytoplasm (Bianciotto et al 1996). Several of these bacteria have beneficial effects on the performance of AMF, including the promotion of fungal spore germination (Mayo et al 1986;Xavier and Germida 2003) and hyphal growth (Hildebrandt et al 2002), the colonization of roots (Mamatha et al 2002), and even the formation of new fertile spores independent of the host plant (Hildebrandt et al 2002;Hildebrandt et al 2006).…”
Section: Introductionmentioning
confidence: 98%
“…Actinobacteria were often found to be associated with AMF spores. Mugnier and Mosse (1987) reported that G. mosseae spores germinated in vitro only in the presence of microorganisms, including Streptomyces orientalis and Ames et al (1989) found that out of 190 spores examined, 100 were colonized by one or more chitin-decomposing microorganisms; 82% were colonized by actinomycetes, 17% by bacteria, and 1% by fungi. Actinomycetes found from the rhizosphere of field grown plants Trifolium repens L. (Franco-Correa et al, 2010) was able to improve plant growth and nutrition, and benefit root colonization by AM fungi.…”
Section: Introductionmentioning
confidence: 99%